Is it Useful to Repeat Magnetic Resonance Imaging of the Sacroiliac Joints After Three Months or One Year in the Diagnosis of Patients With Chronic Back Pain and Suspected Axial Spondyloarthritis?. Issue 3 (6th February 2019) - Bakker, P. A. C.; Ramiro, S.; Ez‐Zaitouni, Z.; van Lunteren, M.; Berg, I. J.; Landewé, R.; Ramonda, R.; van Oosterhout, M.; Reijnierse, M.; van Gaalen, F. A.; van der Heijde, D.
Abstract : Objective: To investigate the value of repeated magnetic resonance imaging (MRI) of the sacroiliac (SI) joints in diagnosing chronic back pain patients in whom axial spondyloarthritis (SpA) is suspected and to examine determinants of positive MRI findings in SI joints. Methods: Patients with chronic back pain (duration 3 months–2 years, age ≥16 years, age at onset <45 years) with ≥1 SpA feature who were included in the Spondyloarthritis Caught Early cohort underwent visits at baseline, at 3 months, and at 1 year. Visits included an evaluation of all SpA features and repeated MRI of SI joints. MRI‐detected axial SpA positivity (according to the definition from the Assessment of SpondyloArthritis international Society) was evaluated by 2 or 3 well‐trained readers who were blinded with regard to clinical information. The likelihood of a positive MRI finding at follow‐up visits (taking into consideration contributing factors) was calculated by generalized estimating equation analysis. Results: Of the 188 patients, 38.3% were male, the mean ± SD age was 31.0 ± 8.2 years, and the mean ± SD symptom duration was 13.2 ± 7.1 months. Thirty‐one patients (16.5%) had positive MRI findings in the SI joints at baseline. After 3 months and after 1 year, the MRI results had changed from positive to negative in 3 of 27 patients (11.1%) and 11 of 29 patients (37.9%), respectively, which was attributable in part to the initiation of anti–tumor necrosis factor therapy. Status changes from negative to positive were seen in 5 of 116 patients (4.3%) after 3 months and in 10 of 138 patients (7.2%) after 1 year. HLA–B27 positivity and male sex were independent determinants of the likelihood of a positive MRI scan at any time point (42% in HLA–B27+ men and 6% in HLA–B27− women). If the baseline results were negative, the likelihood of a positive scan at follow‐up was very low (≤7%). Conclusion: MRI‐detected status changes in the SI joints were seen in a minority of the patients, and both male sex and HLA–B27 positivity were important predictors of MRI positivity. Our findings indicate that conducting MRI scans after 3 months or after 1 year in patients with suspected early axial SpA is not diagnostically useful.